PENGARUH KEPEMILIKAN KELUARGA TERHADAP BIAYA AUDIT DENGAN PILIHAN AUDITOR SEBAGAI VARIABEL INTERVENING - Ajeng Primasari; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to determine the effect of family ownership on audit fees wuth auditor choices as intervening variable. This study uses secondary data which sourced from Indonesia Stock Exchange period 2013-2015. The populations in this study are 413 manufacturing companies which listed on Indonesia Stock Echange. Based on the criterias which had been specified, the samples of this study are 118 manufacturing companies. The method of analysis uses in this study are logistic regression analysis, linear regression analysis, and path analysis. The results show that variable of family ownership has positive effect on variable of auditor choices. Variable of auditor choices has positive effect on variable of audit fees. Variable of family ownership has negative effect on variable of audit fees with variable of auditor choice as intervening variable.